To Evaluate the Role of Bone Marrow Aspiration and Bone Marrow Biopsy in Pancytopenia - Melina Desalphine; Permeet Kaur Bagga; Parmod Kumar Gupta; Amarjit Singh Kataria (Journal of Clinical and Diagnostic Research, 2014)
Background: Pancytopenia is not a disease entity but a triad of findings that may result from various disease processes, primarily or secondarily involving the bone marrow. Bone marrow aspiration and biopsy evaluation along with good clinical correlation is of utmost importance to evaluate the causes of pancytopenia and planning further investigations. Aims: The present study was a prospective clinicohaematological study undertaken to analyse the various causes of pancytopenia by evaluating bone marrow aspiration and biopsy and correlating with clinical findings, complete blood counts and peripheral blood picture. Materials and Methods: Fifty patients of pancytopenia were included in the study in which relevant history and physical examination findings were recorded. Bone marrow aspiration and biopsy were performed simultaneously in all cases. Perl’s stain was done in all cases and special stains like MPO, PAS and reticulin were also done wherever necessary. Results and Conclusion: The maximum cases of pancytopenia were in the age group of 10 to 30 y with male preponderance. Aplastic anaemia was found to be the most common aetiology of pancytopenia followed by normoblastic erythroid hyperplasia, megaloblastic anaemia, acute leukemias, myelofibrosis, lymphoid neoplasia and iron deficiency anaemia. It was concluded from the study that although the advantages of bone marrow aspiration and biopsy differ, both are complimentary to each other and should be performed simultaneously for a complete bone marrow work up and evaluation. It is only through the correlation of clinical, hematological and bone marrow examination findings that proper evaluation and management of patients of pancytopenia can be made.